Coordinated Activity in the Brain Measurements and Relevance to Brain Function and Behavior - Velazquez, Jose Luis Perez; Wennberg, Richard (Springer Series in Computational Neuroscience, 2009)
Increasing interest in the study of coordinated activity of brain cell ensembles reflects the current conceptualization of brain information processing and cognition. It is thought that cognitive processes involve not only serial stages of sensory signal processing, but also massive parallel information processing circuitries, and therefore it is the coordinated activity of neuronal networks of brains that give rise to cognition and consciousness in general. While the concepts and techniques to measure synchronization are relatively well characterized and developed in the mathematics and physics community, the measurement of coordinated activity derived from brain signals is not a trivial task, and is currently a subject of debate. Coordinated Activity in the Brain: Measurements and Relevance to Brain Function and Behavior addresses conceptual and methodological limitations, as well as advantages, in the assessment of cellular coordinated activity from neurophysiological recordings. The book offers a broad overview of the field for investigators working in a variety of disciplines (neuroscience, biophysics, mathematics, physics, neurology, neurosurgery, psychology, biomedical engineering, computer science/computational biology), and introduces future trends for understanding brain activity and its relation to cognition and pathologies. This work will be valuable to professional investigators and clinicians, graduate and post-graduate students in related fields of neuroscience and biophysics, and to anyone interested in signal analysis techniques for studying brain function J. L. Perez Velazquez was born in Zaragoza, Spain, and received the degree of 'Licenciado' in Chemistry (Biochemistry, universities of Zaragoza and Complutense of Madrid), and a PhD degree in 1992 from the Department of Molecular Physiology and Biophysics at Baylor College of Medicine (Houston), homologated to Doctorate in Chemistry by the Spanish Ministry of Culture in 1997. He is an Associate Scientist in the Neuroscience and Mental Health Programme and the Brain and Behaviour Centre at the Hospital For Sick Children in Toronto, and an Associate Professor at the University of Toronto. Richard Wennberg was born in Vancouver, Canada. He obtained his medical degree from the University of British Columbia in 1990 and completed a neurology residency at McGill University in 1994, followed by a fellowship in electroencephalography at the Montreal Neurological Institute. He is Director of the clinical neurophysiology laboratory at the University Health Network, Toronto Western Hospital; Associate professor of Medicine at the University of Toronto; Chair of the Royal College of Physicians and Surgeons of Canada examination board in neurology, and President of the Canadian League Against Epilepsy.